Treatment outcomes in oropharynx cancer patients who did not complete planned curative radiotherapy. (October 2019) - Alfaraj, Fatimah; Craig, Tim; Huang, Shao Hui; O'Sullivan, Brian; Su, Jie; Bayley, Andrew; Bratman, Scott; Cho, John; Giuliani, Meredith; Kim, John; Ringash, Jolie; Waldron, John; et al.
Highlights: HPV-positive status was associated with a higher OS. HPV-positive patients who received BED10 ≥55 had higher OS than those received BED10 <55. HPV-negative group has poor survival even with BED10 ≥55. TD50 (BED10) was estimated at 27.2 Gy for HPV-positive patients. Abstract: Purpose: To evaluate outcomes in oropharyngeal cancer (OPC) patients who did not complete their planned curative radiation therapy (RT). Methods: OPC Patients who received less than planned curative RT dose between 2002 and 2016 were identified for analysis. HPV status was assessed. Radiation dose was normalized for fractionation variations using biological effective doses assuming tumor α/β = 10 Gy [BED10]. Outcomes were compared using BED10. Multivariable and univariable analysis identified OS predictors. Results: From a total of 80 patients who did not complete therapy, 64 patients were eligible for analysis. RT incompletion was due to: RT side effects (n = 23), patients' decision (n = 21), disease progression or metastases (n = 3), and other causes (n = 7). Median BED10 (Gy) was 56.2 for the HPV-positive and 58 for the HPV-negative. Three-year OS was 74% vs 13% (p < 0.001) for the HPV-positive (n = 29) and HPV-negative (n = 24), respectively. HPV-positive patients who received BED10 ≥55 had higher OS than those received BED10 <55 (94% vs 47%, p = 0.002) while no difference in OS by BED10 ≥55 vs <55 for the HPV-negative (12 vs 13%, p = NS). HPV-positive status was associated with a higher OS (HR 12.5, 95% CI, 4.54 to 33.3, p < 0.001). A total of 37 patients were available to estimate TD50 for local control assessment. TD50 (BED10) was estimated at 60.5 Gy for HPV-negative patients compared to 27.2 Gy for HPV-positive patients. Conclusion: Overall, in patients with incomplete treatment, HPV-positive OPC patients demonstrated a better OS compared to HPV-negative patients. HPV-positive patients who received BED10 ≥55 have higher rates of OS.